2021
DOI: 10.1088/1757-899x/1166/1/012055
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and Magnetic Studies La+3 doped Cobalt Nano Ferrite

Abstract: La3+ substituted cobalt ferrite nano-particles with the chemical composition LaxCoFe2-xO4 (here,x=0, 0.05, 0.1, 0.15 and 0.2) were synthesized using auto-combustion method. Structural and morphological studies were probed using X-ray diffraction (XRD) and Field Emission Scanning Electron Microscopy (FESEM). Formation of rare-earth doped cobalt ferrite was confirmed using the X-ray diffraction studies. Average crystallite size (D) was found to be varying from 43.71nm to 55.37nm with the increase in La3+ concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Lowerfrequency dielectric behavior is attributed to space charge polarization, which is consistent with Koop's phenomenological theory. [22,23] According to this theory, the dielectric material is made of conducting grains separated by high-resistive grain boundaries, and it is also observed that grains are more active at high frequencies and grain boundaries are more at low frequencies. Small dielectric constant values at high frequencies may be caused by electron hopping between Fe 2þ and Fe 3þ ions, which cannot follow the change in the applied AC electric field.…”
Section: Resultsmentioning
confidence: 99%
“…Lowerfrequency dielectric behavior is attributed to space charge polarization, which is consistent with Koop's phenomenological theory. [22,23] According to this theory, the dielectric material is made of conducting grains separated by high-resistive grain boundaries, and it is also observed that grains are more active at high frequencies and grain boundaries are more at low frequencies. Small dielectric constant values at high frequencies may be caused by electron hopping between Fe 2þ and Fe 3þ ions, which cannot follow the change in the applied AC electric field.…”
Section: Resultsmentioning
confidence: 99%